Occult community acquired Klebsiella pneumoniae purulent meningitis in an adult: A case report. Issue 25 (June 2018) - Yang, Kai-Chuang; Shrestha, Tejashwi; Kolakshyapati, Manish; Shi, Ling-Fei; Wang, Zheng; Li, Min; Lou, Lin; Zhou, Jia
Abstract: Rationale: Klebsiella pneumonia (K. pneumonia), primarily a hospital-acquired pathogen, can cause a variety of deep-seated infections with significant morbidities. However, in the current scenario of global rise in antibiotic abuse, unexpected infection could be caused by K. pneumoniae. Patient concerns: A 56-year-old male who presented with intermittent headache and low fever was admitted, he had transsphenoidal surgery for pituitary adenoma 3 years ago. Routine laboratory tests revealed an elevated WBC count of 10.12 × 10 9 /L and C-reactive protein (CRP) 12.9 mg/L. computed tomography (CT) revealed the sellar region with suspicious hemorrhage. Diagnoses: The patient was initially diagnosed with acute residual tumor hemorrhage. But the consequent diagnose of Klebsiella pneumoniae purulent meningitis was made based on the cerebrospinal fluid lab test and cerebrospinal fluid (CSF) and blood culture, and CT scan. Interventions: Lumbar puncture examination was made and the antibiotics were adjusted to meropenem and vancomycin according to the antibiotic sensitivity test. But because of the patient's unstable vital signs, his family refuse further lateral ventricular drainage. Outcomes: The infection was out of control and the patient died of spontaneous breath and heartbeat arrest. Lessons: Through this case, we could learn that any clue of suspicious intracranial infection should be carefully considered in the current scenario of global rise in antibiotic abuse. The manifestation of intermittent headache and mild fever could be potential signs of fatal infection, and prompt appropriate measures should be taken timely.